LGBT 'Communities' and the (Self-)regulation and Shaping of Intimacy. (March 2022) - Formby, Eleanor
This article draws on UK research with over 600 lesbian, gay, bisexual, and trans (LGBT+) people, funded by the Arts and Humanities Research Council (grant AH/J011894/1), which explored understandings and experiences of LGBT 'community'. I examine the ways in which intimacy is regulated and shaped by and within social interaction, which was apparent in three main ways. First, the research identified how for some people the very concept of 'LGBT community' was linked to intimacy. Second, there was strong evidence to suggest that some LGBT+ people self-regulate their practices of intimacy (such as holding hands or kissing in public) so as not to be recognised as enacting a same-gender relationship. This was understood as a form of self-protection or hate crime prevention, though degrees of habit and professed concern for other people's feelings were also contributing factors. Third, experiences of intimate relations were shaped by intersectional dynamics, particularly relating to various forms of discrimination, including ageism, biphobia, classism, (dis)ableism, racism, and transphobia from and among LGBT+ people. Whilst LGBT 'communities' were thought to enable opportunities to seek sexual and/or intimate encounters, this is not without its complexities. Although there have been improvements in relation to legislation and wider social attitudes, there is, for some, persistent apprehension and self-regulation which, whether necessary or not, are significant. LGBT+ people's experiences thus suggest that intimacy can be shaped by multiple inequalities both within and without LGBT 'communities'.